Natural astaxanthin enhanced antioxidant capacity and improved semen quality through the MAPK/Nrf2 pathway in aging layer breeder roosters - Shan Gao (BMC, 2021)
Abstract Background Natural astaxanthin (ASTA) has strong antioxidant properties and has been widely used as a health product to improve human health. However, the effects of ASTA on the reproductive performance of aging roosters have been poorly studied. We aimed to investigate the effects of dietary ASTA on semen quality and antioxidant capacity in aging roosters and to explore the potential mechanism of semen quality change via anti-oxidation defense system. Methods In the present study, 96 53-week-old Jinghong No. 1 layer breeder roosters were fed a corn-soybean meal basal diet containing 0, 25, 50, or 100 mg/kg ASTA for 6 weeks. Results Semen quality in the ASTA groups remarkably improved than that in the control group, and antioxidant activities, the abilities to scavenge hydroxyl radicals and superoxide anions, increased gradually with ASTA addition (P < 0.05). In addition, the mRNA levels of antioxidant enzymes as well as the mRNA and protein levels of the mitogen-activated protein kinase (MAPK) and nuclear factor-erythroid 2-related factor 2 (Nrf2) were markedly increased in the 50–100 mg/kg ASTA group (P < 0.05). Conclusions Collectively, these results demonstrate that dietary ASTA may improve semen quality by increasing antioxidant enzyme activities and the ability to scavenge hydroxyl radicals, which may be related to upregulation of the MAPK/Nrf2 pathway.